2021
DOI: 10.1371/journal.pone.0245148
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing proteins in the leaves of cork oak plants associated with the immune response to Phytophthora cinnamomi inoculation in the roots: A long-term proteomics approach

Abstract: The pathological interaction between oak trees and Phytophthora cinnamomi has implications in the cork oak decline observed over the last decades in the Iberian Peninsula. During host colonization, the phytopathogen secretes effector molecules like elicitins to increase disease effectiveness. The objective of this study was to unravel the proteome changes associated with the cork oak immune response triggered by P. cinnamomi inoculation in a long-term assay, through SWATH-MS quantitative proteomics performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 88 publications
2
11
0
Order By: Relevance
“…Plant leaves can be an important tissue for practical monitoring of infection or resistance. An extensive change in the proteome profile of leaves in response to root infection by soilborne pathogen has been reported before ( Coelho et al, 2021 ). Our results here showed that in both cultivars the amount of chlorophyll content significantly ( p < 0.01) reduced after infection.…”
Section: Resultssupporting
confidence: 52%
“…Plant leaves can be an important tissue for practical monitoring of infection or resistance. An extensive change in the proteome profile of leaves in response to root infection by soilborne pathogen has been reported before ( Coelho et al, 2021 ). Our results here showed that in both cultivars the amount of chlorophyll content significantly ( p < 0.01) reduced after infection.…”
Section: Resultssupporting
confidence: 52%
“…Further use of the iTRAQ method will allow the elucidation of the molecular mechanisms that underlie elicitin-triggered immunity [51]. A study using another proteome tool, SWATH-MS (Sequential Window Acquisition of All Theoretical Mass Spectra) [52], revealed the differential expression of 80 proteins in Q. suber infected with P. cinnamomi that provided insights into the association between pathogen invasion and the subsequent plant response. Another technique that holds prospects for the identification of elicitin functions and proteome relationships is shotgun proteomics [53], which has been used, for example, to detect over 500 different peptides in culture filtrates of the mycorrhizal fungus Rhizophagus irregularis, and which has greatly expanded our knowledge of proteins that are involved in the establishment of symbiosis [54].…”
Section: Proteomic Approachesmentioning
confidence: 99%
“…References: 1, Song et al (2015) ; 2, Noël et al . (2007) ; 3, Lyu et al (2020) ; 4, Wu et al (2019) ; 5, Góngora-Castillo et al (2012) ; 6, Saiz-Fernández et al (2020) ; 7, Gupta et al (2017) ; 8, Klink et al (2007) ; 9, Berka et al (2020) ; 10, Molitor et al (2011) ; 11, Sharma Poudel et al (2019) ; 12, C. Zhang et al (2015) ; 13, Ye et al (2011) ; 14, Hafrén et al (2010) ; 15, Caplan et al (2009) ; 16, Hýsková et al (2021b) ; 17, Crampton et al (2009) ; 18, Cerna et al (2017) ; 19, Coelho et al (2021) ; 20, Singh et al (2019) ; 21, Vitale et al (2014) ; 22, Naveed and Ali (2018) ; 23, Gorovits et al (2013) ; 24, Chen et al (2013) ; 25, Pan et al (2013) ; 26, Szajko et al (2020) ; 27, Guo et al (2021) ; 28, Yang et al (2017) ; 29, Paiva et al (2016) ; 30, Varela et al (2017) ; 31, Liu et al (2021) ; 32, Chen et al (2017) .…”
Section: Introductionmentioning
confidence: 99%